Histamine Increases Th2 Cytokine-Induced CCL18 Expression in Human M2 Macrophages - Susanne Mommert (MDPI AG, 2021)
The chemokine CCL18 is produced in cells of the myelomonocytic lineage and represents one of the most highly expressed chemokines in lesional skin and serum of atopic dermatitis patients. We investigated the role of histamine in CCL18 production in human monocyte-derived M2 macrophages differentiated in the presence of M-CSF and activated with IL-4, IL-13 or with IL-10. Since expression and regulation of histamine H1 receptor (H1R), H2R and H4R by IL-4 and IL-13 on human M2 macrophages were described, we analyzed expression of the histamine receptors in response to IL-10 stimulation by quantitative RT-PCR. IL-10 upregulated H2R and downregulated H4R mRNA expression by trend in M2 macrophages. IL-10, but in a more pronounced manner, IL-4 and IL-13, also upregulated CCL18. Histamine increased the cytokine-induced upregulation of CCL18 mRNA expression by stimulating the H2R. This effect was stronger in IL-10-stimulated M2 macrophages where the upregulation of CCL18 was confirmed at the protein level by ELISA using selective histamine receptor agonist and antagonists. The histamine-induced CCL18 upregulation in IL-10-activated M2 macrophages was almost similar in cells obtained from atopic dermatitis patients compared to cells from healthy control persons. In summary, our data stress a new function of histamine showing upregulation of the Th2 cells attracting chemokine CCL18 in human, activated M2 macrophages. This may have an impact on the course of atopic dermatitis and for the development of new therapeutic interventions.